(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Blockchain technology has emerged as a promising solution for enhancing the security and management of medical records in the healthcare industry. This article provides a detailed examination of how blockchain technology works, its application in medical record management, benefits, challenges, and future prospects. By leveraging blockchain’s decentralized and immutable nature, healthcare organizations can address issues related to data security, interoperability, and patient privacy, ultimately improving the quality of care delivery.